Exploring uncertainty in the calibration of the molecular clock - Warnock, Rachel C. M.; Yang, Ziheng; Donoghue, Philip C. J. (Biology Letters, 2012)
Calibration is a critical step in every molecular clock analysis but it has been the least considered. Bayesian approaches to divergence time estimation make it possible to incorporate the uncertainty in the degree to which fossil evidence approximates the true time of divergence. We explored the impact of different approaches in expressing this relationship, using arthropod phylogeny as an example for which we established novel calibrations. We demonstrate that the parameters distinguishing calibration densities have a major impact upon the prior and posterior of the divergence times, and it is critically important that users evaluate the joint prior distribution of divergence times used by their dating programmes. We illustrate a procedure for deriving calibration densities in Bayesian divergence dating through the use of soft maximum constraints. © 2011 The Royal Society.
CRIS-Team Scopus Importer:2020-10-13
Keywords: BEAST; Calibration; Evolution; Fossil record; MCMCTREE; Molecular clock